(untitled) - Vercel, Roger (Paris, 1952)
A very good unopened copy, wrappers soiled. Paper wrappers. Sm. 8vo. 328 pp. In French. Garnier was a nineteenth century explorer in Southeast Asia who spent much time along the Mekong River
Keywords: Đông Dương,Indochina; Lịch sử,History